Therapeutic potential and nutritional significance of Ganoderma lucidum – a comprehensive review from 2010 to 2022. Issue 4 (3rd February 2023) - Swallah, Mohammed Sharif; Bondzie-Quaye, Precious; Wu, Yahui; Acheampong, Adolf; Sossah, Frederick Leo; Elsherbiny, Shereen M.; Huang, Qing
Abstract : The medicinal reputation of Ganoderma lucidum and its unique pharmaceutical and nutritional properties have led to its demand as an important resource for nutrient supplements in the food industry. Abstract : With a long history in traditional Asian medicine, Ganoderma lucidum ( G. lucidum ) is a mushroom species suggested to improve health and extend life. Its medicinal reputation has merited it with numerous attributes and titles, and it is evidenced to be effective in the prevention and treatment of various metabolic disorders owing to its unique source of bioactive metabolites, primarily polysaccharides, triterpenoids, and polyphenols, attributed with antioxidant, anti-inflammatory, anticancer, hepatoprotective, antidiabetic activities, etc . These unique potential pharmaceutical properties have led to its demand as an important resource of nutrient supplements in the food industry. It is reported that the variety of therapeutic/pharmacological properties was mainly due to its extensive prebiotic and immunomodulatory functions. All literature summarized in this study was collated based on a systematic review of electronic libraries (PubMed, Scopus databases, Web of Science Core Collection, and Google Scholar) from 2010–2022. This review presents an updated and comprehensive summary of the studies on the immunomodulatory therapies and nutritional significance of G. lucidum, with the focus on recent advances in defining its immunobiological mechanisms and the possible applications in the food and pharmaceutical industries for the prevention and management of chronic diseases. In addition, toxicological evidence and the adoption of standard pharmaceutical methods for the safety assessment, quality assurance, and efficacy testing of G. lucidum -derived compounds will be the gateway to bringing them into health establishments.